Penggunaan Bahasa Nonverbal dalam Upacara Adat Pernikahan Gaya Yogyakarta: Kajian Simbolik Etnopragmatik - NFN Pranowo; Winci Firdaus (Ranah: Jurnal Kajian Bahasa, 2020)
This research is an interpretive reflective research with ethnopragmatic symbolic study theory. The source of the research data was taken from the documents of two makeup artists from Yogyakata, namely the makeup dresser Lisandra and the makeup dresser Hj. Rochayati. The research data are in the form of Javanese traditional wedding document of Yogyakarta style. The data collection technique is in the form of observation of photo documentation to obtain data in the form of a marriage ceremony sequence that uses verbal and nonverbal language from preparation to the end. The data analysis technique is interpretive reflective. The concrete steps of data analysis are (a) identifying documents, (b) classifying the sequences of marriages, and (c) interpreting each stage of the ceremony. The objectives of the research are (1) to describe the form of nonverbal language in traditional marriage ceremonies, and (2) to describe the non-verbal symbolic meaning of non-verbal language in marriage ceremonies. The findings of the research are that (a) the form of Yogyakarta-style traditional wedding events there are 15 stages, ranging from paningsetan to reception, and (b) ethnopragmatic symbolic meaning in general in the form of prayer requests so that what is desired can be realized.AbstrakPenelitian ini merupakan penelitian reflektif interpretatif dengan teori kajian simbolik etnopragmatik. Sumber data penelitian diambil dari dokumen dua orang juru rias dari Yogyakata, yaitu rias pengantin Lisandra dan rias penantin Hj. Rochayati (nama disamarkan). Data penelitian berupa dokumen foto perkawinan adat Jawa gaya Yogyakarta. Teknik pengumpulan data berupa observasi dokumentasi foto untuk mendapatkan data berupa urutan upacara perkawinan yang menggunakan bahasa verbal dan bahasa nonverbal dari persiapan sampai dengan akhir. Teknik analisis data dilakukan secara reflektif interpretatif. Langkah konkret analisis data adalah (a) mengidentifikasi dokumen, (b) mengklasifikasi urut-urutan acara perkawinan, dan (c) menginterpretasi tiap tahapan upacara. Tujuan penelitiannya adalah (1) mendeskripsikan wujud bahasa nonverbal dalam upacara adat perkawinan, dan (2) mendeskripsikan makna simbolik etnopragmatik bahasa nonverbal dalam upacara adat perkawinan. Temuan hasil penelitian adalah bahwa (a) wujud acara adat perkawinan gaya Yogyakarta terdapat 15 tahapan, mulai dari paningsetan sampai dengan resepsi, dan (b) makna simbolik etnopragmatik pada umumnya berupa doa permohonan agar apa yang diinginkan dapat terwujud.